Seed germination methods of benuang laki (Duabanga moluccana) seeds at the laboratory and greenhouse - Evayusvita Rustam; Dede J. Sudrajat (Jurnal Penelitian Kehutanan Wallacea, 2022)
Benuang laki (Duabanga moluccana) is a potential fast-growing tree species to be developed in plantation forests, community forests, and land rehabilitation. This species has a very fine seed size that requires special treatment in germination, both in testing activities in the laboratory and operational activities in the nursery. The purpose of this study was to determine the optimum germination technique for benuang laki seeds in the laboratory and greenhouse. A completely randomized design arranged with a factorial pattern was used to determine the effect of the test method and lighting period in the laboratory, and the effect of sowing media and germination conditions in the greenhouse. To obtain a reliable and reproducible germination method, the tests were carried out involving 3 seed lots. The results showed that the top-of-paper test method with a lighting period of 24 hours resulted in the highest germination capacity and germination rate, i.e., Semboja (415 seedlings/0.05 g and 30.17 seedlings/day), Cianjur (253 seedlings/0.05 g and 19.47 seedlings/day), and Rarung (158 seedlings/0.05 g and 12.34 seedlings/day), respectively. The highest germination in the greenhouse was produced by the treatment of sand + topsoil (1:1, v/v) media covered with transparent plastic, with a germination capacity of 870 seedlings/0.1 g of seed and a germination rate of 28.13 seedlings/day.